ERGONOMICS AS A SAFETY FACTOR IN THE RAILWAY INDUSTRY - Vorozhbiian, М.; Brusentsov, V.; Ivashchenko, М.; Skrypnyk, О. (Municipal economy of cities. Series: «Economy science», 2023)
Railway transport is a huge energetic system, the functioning of which is determined by the coordinated work of thousands of employees of various specialties, including dispatchers and locomotive drivers. In the "man-technical system-production environment" system, a person is the "weakest link", determining the reliability and safety of the system's functioning as a whole. Studies show that the driver's work in conditions of high-speed traffic involves a high level of stress on the nervous analyzers, as well as the functions of memory and attention, which leads to their rapid fatigue. The level of fatigue obtained as a result of the work shift is unacceptable for most workers, monitoring the level of functional reliability of the worker can be an effective means of combating accumulated fatigue. The problems of ensuring the normal life of workers in dangerous professions in modern social and industrial conditions are caused primarily by the intense influence of negative social, professional and other factors that cause the development of adverse mental states and overstrain of psychophysiological functions. All this creates stressful situations, both in society in general and for every person. Of course, in addition to the above-mentioned stresses, an important place in the activity of a human operator is occupied by professional stress, which is constantly present. The systemic impact of stress has both an immediate and remote nature. Experimental studies have established that it reduces the level of functional reliability of the "human operator". Such states include, first of all, fatigue, stress and borderline states (between health and illness). Such indicators can be an indicator of high danger of such a relevant phenomenon for the transport industry as sudden ischemic death. A distinction is made between the slow and operational components of performance, while the slow (trend) does not change for a long time (month, years), and the operational (functional state) changes in the form of "peaks", "declines" or a relatively flat "plateau" during hours. It follows from this that in order to maintain the appropriate level of safety of the transport process, it is necessary to implement control of the level of efficiency of railway operators, including its trending part, taking into account the presence of constant stresses today. It is necessary to conduct monitoring as a prediction of early diagnosis of changes in the functional state of operators, and therefore the state of professional reliability.